A Project Report on Hue Preserving Color Image Enhancement Using Multiscale Morphology - ABDUL RAZAK, CHETHN R and JAYAPRAKASH S R (2012)
INTERNAL GUIDE: MALAVIKA T, MVJCE
Keywords: Enhancement Using Multiscale Morphology